Late Weichselian periglacial features in south-eastern Finland and the surroundings of Lake Ladoga in Russia - J. Donner; I. Delusin (Bulletin of the Geological Society of Finland, 1995)
Ice-wedge casts recorded from the Salpausselkä moraines in south-eastern Finland show that there was permafrost in this zone at the time of the Younger Dryas Stadial. The few sites with pocket involutions north and east of Lake Ladoga indicate that even this area had permafrost at the same time. Other signs of a periglacial environment are the stone pavements with ventifacts, underneath coversands, both in the Salpausselkä zone as well as outside it. Coversands and dunes were accumulated before a closed vegetation covered the area in the beginning of the Holocene.